VIVÊNCIAS E RESIGNIFICAÇÕES DE PARTOS DOMICILIARES HUMANIZADOS EM GUARAPUAVA-PR - Corso, Marjorie Rabel (2020)
The city of Guarapuava, in the state of Paraná, a is a major center active in the health área, being de headquarters of the 5th Regional Health and reference for more than 20 neighboring cities. The two main hospitals in Guarapuava have maternity hospitals and perform a large number of deliveries, however, both do not have the humanization of delivery as their main characteristic, which was demonstrated by the high rate of cesarean sections performed in the city. Four women were interviewed in February and March 2019 and, through oral history, narrated their experiences and feelings regarding humanized childbirth, performed in the city of Guarapuava. Among them, one acts as a doula and the other as an obstetric nurse in the humanized birth network that recently started to form in the city. The narratives made it possible to open up discussions about excessive medicalization, disrespect for women’s reproductive and sexual rights and the lack of protagonism of women in the act of giving birth, as well as analyzing the sphere of power that involves the phenomenon of childbirth, among professional health and parturient women. The narratives of the women interviwed provided an investigation into the motivations for the search for a humanized delivery, alerting to the obstetric violence suffered in this intimate and fragile moment, in addition, they evidenced the experience of four women who chose their mode of delivery as an act of protagonism by giving birth, subverting the technocratic system that permeated the social phenomenon of childbirth. The research suggestes that changes are necessary in the health system as a whole, expanding access to maternity hospitals and ensuring dignified and respectful care for women, highlighting the role of nursing professional in this process of welcoming and managing the pain of labor.